The Routledge handbook of service user involvement in human services research and education - McLaughlin, Hugh, 1954- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Worldwide there has been a growth in service user involvement in education and research in recent years. This handbook is the first book which identifies what is happening in different regions of the world to provide different countries and client groups with the opportunity to learn from each other. Divided into five sections and providing forty-eight chapters including seventeen case-studies from all regions of the world, this is the first book to both highlight the subject's methodological and theoretical issues as well as giving practical examples in education and research for those wishing to engage in this field. It will be of interest to all service users, scholars and students of social work, nursing, occupational therapy, and other human service subjects"--
OCLC-licensed vendor bibliographic record.
Keywords: Human services -- Research; Social service -- Research; Participant observation; SOCIAL SCIENCE / Social Work